An algebra problem by avn bha

Algebra Level 3

1 ( x 1 ) ( x 2 ) + 1 ( x 2 ) ( x 3 ) + 1 ( x 3 ) ( x 4 ) = 1 6 \frac{1}{(x-1)(x-2)} + \frac{1}{(x-2)(x-3)} + \frac{1}{(x-3)(x-4)} = \frac{1}{6}

What is the sum of all real values of x x that satisfy the above equation?


The answer is 5.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

5 solutions

U Z
Feb 8, 2015

We have the equation

1 ( x 1 ) ( x 2 ) + 1 ( x 3 ) ( x 2 ) + 1 ( x 3 ) ( x 4 ) = 1 6 \dfrac{1}{(x - 1)(x - 2)} + \dfrac{1}{(x - 3)(x - 2)} + \dfrac{1}{(x - 3)(x - 4)} = \dfrac{1}{6}

Making some adjustment and solving it further:

( x 1 ) ( x 2 ) ( x 1 ) ( x 2 ) + ( x 2 ) ( x 3 ) ( x 3 ) ( x 2 ) + ( x 3 ) ( x 4 ) ( x 3 ) ( x 4 ) = 1 6 \dfrac{(x - 1) - (x - 2)}{(x - 1)(x - 2)} + \dfrac{(x - 2) - (x - 3)}{(x - 3)(x - 2)} + \dfrac{(x - 3) - (x - 4)}{(x - 3)(x - 4)} = \dfrac{1}{6}

1 x 2 1 x 1 + 1 x 3 1 x 2 + 1 x 4 1 x 3 = 1 6 \dfrac{1}{x - 2} - \dfrac{1}{x - 1} + \dfrac{1}{x - 3} - \dfrac{1}{x - 2} + \dfrac{1}{x - 4} - \dfrac{1}{x - 3} = \dfrac{1}{6}

1 x 4 1 x 1 = 1 6 \dfrac{1}{x - 4} - \dfrac{1}{x - 1} = \dfrac{1}{6}

18 = ( x 4 ) ( x 1 ) 18 = (x - 4)(x - 1)

x 2 5 x 14 = 0 x^2 - 5x - 14 =0

we have the discriminant Δ = 81 > 0 \Delta=81\gt 0 , so both the roots of the quadratic are real and distinct.

By vieta's , sum = ( 5 ) 1 = 5. \dfrac{-(-5)}{1} = 5.\square

Note that in general, you cannot simply use Vieta's formulas without first checking the nature of the roots. In this case, we have the discriminant Δ = 81 > 0 \Delta=81\gt 0 , so both the roots of the quadratic are real and distinct.

Now, you can use Vieta's formulas to find the required root sum.

Prasun Biswas - 6 years, 4 months ago

Log in to reply

Not necessary to find the discriminant , we can easily say by the sign of constant i.e c ( here -12) and a i.e (+1) , thus -4ac will be positive so discriminant will be greater than zero , thus it will have real and distinct roots . Thanks

U Z - 6 years, 4 months ago

Log in to reply

yeah right constant is negative so discriminant will always be greater than zero . no need to check.Nice solution

Gautam Sharma - 6 years, 4 months ago

Yes, but including this reasoning in your solution would've been nice.

Prasun Biswas - 6 years, 4 months ago

Log in to reply

@Prasun Biswas Agree with you

Gautam Sharma - 6 years, 4 months ago

Prasun is correct, Vieta's formula includes complex roots as well. Otherwise, great solution!

Ryan Tamburrino - 6 years, 4 months ago

Nice, except the last equation should be x 2 5 x 14 = 0 x^2 - 5x - 14 = 0 , so therefore x = 2 , 7 x = -2, 7 .

Ariel Gershon - 6 years, 4 months ago

Log in to reply

Thanks for noticing

U Z - 6 years, 4 months ago

For ax^2+bx+c=0, if a and c have opposite signs, then Delta is always positive. In this case 1 and (-14) are opposite in sign, so there is no need to calculate Delta.

Nguyen Tra - 6 years, 4 months ago

I see what you are saying, but if you plug in 5 for x, it does not work. it does work for 7 though..

Simone Sweatman - 6 years, 3 months ago

Log in to reply

5 is the sum of roots

U Z - 6 years, 3 months ago

Please read the question carefully before commenting. The question clearly states that you have to answer the sum of all real values of x x that satisfies the given equation.

Prasun Biswas - 6 years, 3 months ago

Nice and easy one.......

Debmalya Mitra - 5 years, 10 months ago

Why don't you simply solve the equation and sum the two roots?

Alias Alterego - 5 years, 2 months ago
Daniel Ferreira
Feb 23, 2015

Desenvolvendo a equação,

( x 2 7 x + 12 ) + ( x 2 5 x + 4 ) + ( x 2 3 x + 2 ) ( x 1 ) ( x 2 ) ( x 3 ) ( x 4 ) = 1 6 3 ( x 2 5 x + 6 ) ( x 1 ) ( x 2 ) ( x 3 ) ( x 4 ) = 1 6 3 ( x 2 ) ( x 3 ) ( x 1 ) ( x 2 ) ( x 3 ) ( x 4 ) = 1 6 3 ( x 1 ) ( x 4 ) = 1 6 x 2 5 x + 4 = 18 x 2 5 x 14 = 0 \frac{(x^2 - 7x + 12) + (x^2 - 5x + 4) + (x^2 - 3x + 2)}{(x - 1)(x - 2)(x - 3)(x - 4)}=\frac{1}{6} \\\\ \frac{3(x^2 - 5x + 6)}{(x - 1)(x - 2)(x - 3)(x - 4)} = \frac{1}{6} \\\\ \frac{3(x - 2)(x - 3)}{(x - 1)(x - 2)(x - 3)(x - 4)} = \frac{1}{6} \\\\ \frac{3}{(x - 1)(x - 4)} = \frac{1}{6} \\\\ x^2 - 5x + 4 = 18 \\\\ x^2 - 5x - 14 = 0

Sabemos que a soma das raízes é dada por b a - \frac{b}{a} ; onde a x 2 + b x + c = 0 ax^2 + bx + c = 0 , a 0 a \neq 0 . Daí,

S = b a S = 5 1 S = 5 S = - \frac{b}{a} \\\\ S = - \frac{- 5}{1} \\\\ \boxed{S = 5}

Gamal Sultan
Feb 12, 2015

[1/(x- 2)] - [1/(x- 1)] = 1/(x - 1)(x - 2)

[1/(x- 3)] - [1/(x- 2)] = 1/(x - 2)(x - 3)

[1/(x- 4)] - [1/(x- 3)] = 1/(x - 4)(x - 3)

Adding

[1/(x- 4)] - [1/(x-1)] = 1/6

Then

x^2 - 5x - 14 = 0

The two roots are :

7, -2

their sum = 5

or directly

the sum of roots = -(-5)/1 = 5

Rocco Dalto
Sep 1, 2016

1 ( X J ) ( X J 1 ) = \frac{1}{(X - J) * (X - J -1)} = A X J + B X J 1 \frac{A}{X - J} + \frac{B}{X - J - 1} \implies
A + B = 1 A + B = 1 ( J + 1 ) A + J B = 1 (J + 1) * A + J * B = -1 \implies A = 1 A = -1 a n d and B = 1 B = 1 \implies 1 ( X J ) ( X J 1 ) = \frac{1}{(X - J) * (X - J -1)} = 1 X J 1 \frac{1}{X - J - 1} - 1 X J \frac{1} {X - J} \implies n = 1 3 1 ( X J ) ( X J 1 ) \sum\limits_{n = 1}^3 \frac{1}{(X - J) * (X - J -1)} = = 1 X 4 \frac{1}{X - 4} - 1 X 1 \frac{1} {X - 1} = = 1 6 \frac{1}{6} \implies X 2 5 X 14 = 0 X^2 - 5X - 14 = 0 i m p l i e s implies X 1 , X 2 = 5 + 9 2 X_1,X_2 = \frac{5 +- 9}{2} \therefore X 1 + X 2 = 5 X_1 + X_2 = 5

I n In G e n e r a l General S o l v e Solve f o r for X : X: j = 1 N 1 ( X J ) ( X J 1 ) \sum\limits_{j = 1}^N \frac{1}{(X - J) * (X - J -1)} = = 1 X N 1 \frac{1}{X - N - 1} - 1 X 1 \frac{1}{X - 1} = 1 M \frac{1}{M} M < > 0. M <> 0.

F o r For M > 0 M > 0 w e we h a v e have t h e the r e a l real s o l u t i o n s : solutions:

X 1 , X 2 = ( N + 2 ) ± N ( N + 4 M ) 2 X_1,X_2 = \frac{(N + 2) \pm \sqrt{N * (N + 4 * M)}}{2} a n d and X 1 + X 2 = N + 2 X_1 + X_2 = N + 2

Avn Bha
Feb 9, 2015

take 1/(x-2)as common from the first two terms and then further solve . after that you will observe that (x-2)gets cancelled. then do the same with the next two terms.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...